Using narrative to construct accountability in cases of death after police contact - Baker, David (The Australian and New Zealand journal of criminology, 2019)
This paper examines the use of narrative verdicts in the coronial system in England and Wales to record findings in cases of death after police contact. It uses a dataset of 68 verdicts into such cases in the period 2004-2015. The paper considers how regulation is constructed in a way that makes complex cases comprehensible through narrative. The construction of these narratives is affected by legal structures, institutional structures, but also the structures imposed by narrative convention. The paper argues that the relationships between these structures affect what type of narrative is constructed in the aftermath of a death after police contact. It further suggests that devices within narratives enable the construction of a comprehensible narrative verdict in such cases.